Female basketball game performance is influenced by menstrual cycle phase, age, perceived demands and game-related contextual factors - Gasperi, L.; Sansone, P.; Gómez-Ruano, M.-A.; Lukonaitiene, I.; Conte, D. (Journal of Sports Sciences, 2025)
This study evaluated the influence of physical and perceived game demands, menstrual cycle phase, perceived recovery, individual and game-related contextual factors on competitive performance in professional, female basketball players.